(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article addresses the issues of raising the future generation of our country, training them as well-rounded, humane, and responsible individuals towards society and nature, as well as increasing the activity of highly spiritual youth in the social and political spheres of our country.